2008
DOI: 10.1128/jb.00406-08
|View full text |Cite
|
Sign up to set email alerts
|

VirB3 to VirB6 and VirB8 to VirB11, but Not VirB7, Are Essential for Mediating Persistence ofBrucellain the Reticuloendothelial System

Abstract: The Brucella abortus virB locus contains 12 open reading frames, termed virB1 through virB12, which encode a type IV secretion system. Polar mutations in the virB locus markedly reduce the ability of B. abortus to survive in cultured macrophages or to persist in organs of mice. While a nonpolar deletion of the virB2 gene reduces survival in cultured macrophages and in organs of mice, a nonpolar deletion of virB1 only reduces survival in macrophages, whereas virB12 is dispensable for either virulence trait. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 67 publications
4
63
0
2
Order By: Relevance
“…This is consistent with similar observations on reduced amounts of several VirB proteins in Brucella carrying a deletion of virB8 (17). VirB8 was previously shown to interact with itself, VirB1, VirB4, VirB5, VirB9, VirB10, and VirB11 (16,18,24,39,48,50).…”
Section: Virb8supporting
confidence: 79%
“…This is consistent with similar observations on reduced amounts of several VirB proteins in Brucella carrying a deletion of virB8 (17). VirB8 was previously shown to interact with itself, VirB1, VirB4, VirB5, VirB9, VirB10, and VirB11 (16,18,24,39,48,50).…”
Section: Virb8supporting
confidence: 79%
“…Others have monitored the interaction of phagosomes containing dead and live B. abortus and observed that live bacteria divert its intracellular fate and preserve the morphological structure after infection (3). More recent findings established the critical role of the T4SS machinery in this process (9,12,15). Like previous reports, heat-killed bacteria were completely digested shortly after exposure to dendritic cells (3).…”
Section: Discussionsupporting
confidence: 52%
“…Recent evidence demonstrated that T4SS is critical for Brucella intracellular persistence and trafficking (9,12,15). Furthermore, secreted bacterial antigens are reported to be more protective than cytosolic antigens (47).…”
Section: Irradiated B Melitensis Induces Virulence Factor Expressionmentioning
confidence: 99%
“…VirB7 At localizes predominantly at the outer membrane, but cytoplasmic membrane, pilus-associated, and other extracellular forms also exist (96). In B. pertussis and Brucella abortus, VirB7 homologs also stabilize VirB9-like partners as well as other VirB subunits (78,93). In B. abortus, mature VirB7 lacks an N-terminal Cys residue and thus is not lipid modified.…”
Section: Inner Membrane Channel/scaffold Subunitsmentioning
confidence: 99%
“…In Brucella spp., a VirB T4SS related to that of A. tumefaciens contributes to virulence, although the identification of translocated effector proteins has proven challenging (34,78). Recently, two substrates, VceA and VceC, were identified through the use of CyaA or TEM1 ␤-lactamase fusion assays (Table 1) (76).…”
Section: C-terminal Secretion Signalsmentioning
confidence: 99%